Examination of Early ChildhoodTeachers’ Techniques to Recognize and Assess the Child Before and During the Distance Education - AYDOS, EMİNE HANDE; Türk, Endam Düzyol; YAĞAN, SEVCAN (Özer Daşcan, 2024)
The objective of this study was to examinethe recognition and assessment techniques employed by early childhood teachers both prior to and following the pandemic, utilizing a fundamental qualitative research methodology. 17 early childhood teachers participated in the study using a semi-structured interview form. The study's conclusions are arranged according to several themes. The methods early childhood teachers employ to recognize and assess the child during in-person instruction is the first of these themes. During face-to-face education, teachers used various techniques to get to recognize and assess children, including observation, developmental observation forms, developmental reports, warm-up games, drawing, working with families, anecdotes, sociometry, and portfolio work. However, through the pandemic, it was observed that they started using techniques such as interviews, post-activities assessment, observation, and teacher cooperation. The sudden switch to online education-assessment techniques in the distance education process has resulted in unanticipated challenges and situations for the early childhood teachers as they attempt to implement the teaching process. In this context, inclusive training can be provided to teachers on how to get to know and assess children, covering various situations comprehensively.
Keywords: Early Childhood; Teachers; Distance Education; Recognizing; Assessmen